IMPROVING THE TENTH-GRADE STUDENTS’ READING COMPREHENSION ACHIEVEMENT THROUGH KWL (KNOW-WANT LEARN) STRATEGY - Islamiati, Meni; Angraini, Nike; Iman, Jaya Nur (Global Expert: Jurnal Bahasa dan Sastra, 2023)
The objective of this research was to get empirical evidence of the improving the tenth grade students’ reading comprehension achievement through KWL (Know-Want-Learn) Strategy of narrative text. The population was the tenth grade students at SMK Negeri 2 Palembang. There were 806 students and 60 students were taken as the sample purposively. They were divided into 2 groups. Namely, experimental group and control group. Each group consisted of 30 students. In collecting the data, the test were used (pretest and posttest). The writer used paired sample t-test (pretest- posttest) and independent sample t-test. In conclusion, there was improving using Know-Want-Learn strategy reading comprehension of narrative text, it could be seen from the results of pretest experimental group was 50.73 and the results of the posttest increased to be 78.60. The mean of score pretest and posttest experimental was 13.267. The results of pretest in control group was 48.07. The results posttest increased to be 61.53. The mean of score pretest and posttest control was 6.867. And also there was significant mean difference between the students showed that pretest and posttest experimental group was 78.60 and pretest-posttest control group was 61.53.